Nemesis, the Roman state and the games - Hornum, Michael B. (Religions in the Graeco-Roman World, 1993)
Although Nemesis was already revered in Archaic Greece, the main evidence for worship comes from the Roman Principate. During this period two important facets of the cult were the association of the goddess with the state, and her presence in agonistic contexts. Nemesis, the Roman State and the Games explores these aspects, discerning a possible connection between them. The author begins by discussing the origin and background of the goddess. He then clarifies the ways in which the goddess was enlisted into the service of the Roman emperor and state. Finally, he explains the presence of the goddess almost exclusively at the Roman Munus and Venatio as derived from the function of such games to express the proper order of society. Nemesis represents a significant re-evaluation of the place of Nemesis in the Roman World. The book also provides an invaluable corpus of epigraphic, literary, and iconographic evidence for the goddess.